Dynamic analysis of varus knee using a subject-specific multibody model of the knee before and after osteotomy. (April 2019) - Badie, Fateme; Katouzian, Hamid Reza; Rostami, Mostafa
Highlights: We define a subject-specific 3D multibody model of the knee. This model was used to investigate the osteotomy effects. This model was defined based on MRI of a patient and the finite element solutions. The osteotomy decreased the contact force at the medial cartilage and meniscus. This non-invasive analysis designed to predict the effects of HTO preoperatively. Abstract: Varus misalignment of the hip-knee-ankle angle causes greater loads on the medial compartment of the knee and increases the risk of developing knee osteoarthritis. High tibial osteotomy is a surgical method where the load-bearing axis is shifted laterally. The purpose of this study is to define a subject-specific three-dimensional multibody model of the knee to investigate the effect of osteotomy on cartilages and menisci during the stance phase of gait. It is assumed that osteotomy transfers load-bearing to the lateral parts of the knee. Magnetic resonance images of a patient with varus alignment were used to generate the geometries of the bones, cartilages, and menisci. Then, an experimental approach was used to determine the parameters for the stiffness matrices and compliant contact models of the tibio-menisco-femoral articulations with the use of finite element solutions. As indicated by the research findings, the contact force at the medial cartilage decreased as the load-bearing axis was transferred to the lateral parts. This subject-specific noninvasive analysis of contact force can be considered as a preoperative assessment tool for the surgeon. to predict the effects of high tibial osteotomy and the shifting of the load-bearing axis to the soft tissues of the knee.